Financing of NCD Prevention in LMICs: Vietnam Case Study - Ammar Rashid; Kassim Nishtar; Saba Amjad (Journal of the Pakistan Medical Association, 2026)
Objective: To estimate spending on non-communicable diseases prevention in Vietnam and identify the enablers, challenges and dynamics underpinning population-level NCD prevention spending, with particular focus on tobacco use, harmful use of alcohol, unhealthy diets and physical inactivity. Methods: Primary and secondary data collection was used to examine processes and organizational contexts that shape the formulation of policy and financial frameworks for NCD prevention. The methodology was categorized into three tiers; an academic literature review, scrutiny and analysis of official policy documents and budgetary data on health and NCDs, and in-depth stakeholder interviews with key government officials leading NCD programmes. Government and government-routed donor spending on population level prevention was gauged to estimate NCD prevention spending. Where possible, impact of prevention programmes on disease incidence and risk factors was gauged through available outcome indicators. Results: Vietnam spent an estimated VND 7,926 billion (US2.62 million) on population-level preventive healthcare in 2016, which amounts to less than 0.5% of the total state health budget, with much of it dedicated to infectious diseases. Spending on NCD prevention is not separately budgeted in health budgets. Challenges to NCD financing include low tobacco and alcohol taxation, lack of a comprehensive risk communication programme for NCD risk factors, and inadequate multi-sectoral stewardship for NCD prevention and control. Conclusion: Vietnam has made progress in reorienting its health system to focus on NCDs, but continues to spend a minimal proportion of its substantial health budget on prevention. Vietnam needs to build on successes against infectious disease and enhance fiscal and policy prioritization of population-level NCD prevention. Keywords: Noncommunicable Diseases, Tobacco, Behavior, Employees, Incidence, Risk Factors, Diet, Communication, Tobacco Use, Health Care, Taxes